Halal Certification Assistance as an Effort to Strengthen the MSME Based Halal Industry in Maringgit Village - Lestari, Haifa; Maulida, Sri; Swandari, Fifi; Haliza, Nur; Amirah, Nida (Universitas Islam Malang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in sustaining local economies, yet they face persistent challenges related to product legality, hygienic packaging, and adoption of modern marketing strategies. In Maringgit Village, Hulu Sungai Tengah Regency, most MSMEs specialize in traditional food products such as kue cincin (ring-shaped cake), roti beras (rice bread), kue apam (apem or steamed cake), kue jabuk (jabuk cookies), and kacang gula (sugar-coated peanuts). Although these products are widely consumed locally, their competitiveness in broader markets is limited due to the absence of halal certification, weak branding, and low digital literacy. This community service program aimed to strengthen the capacity of 30 MSMEs by facilitating halal certification while enhancing product identity and marketing strategies. The implementation method combined Participatory Action Research (PAR) to involve MSMEs in identifying problems and solutions, Asset-Based Community Development (ABCD) to optimize local culinary potential as economic capital, and Service Learning (SL) to integrate student participation in mentoring and capacity building. Activities included socialization, administrative assistance for halal certification through the SiHalal system, training on digital marketing and packaging design, provision of halal-compliant production facilities, and structured evaluation. The results showed that 18 MSMEs successfully obtained halal certification from BPJPH, all participants updated product logos and adopted more hygienic packaging, and received production tools such as stoves, pans, woks, presses, containers, and gas cylinders. Social impacts also emerged, including the establishment of the Maringgit Halal MSME Group, the emergence of local leaders, and increased collective awareness of halal industry standards. Overall, the program successfully met its objectives by producing halal-certified products while enhancing MSME competitiveness and institutional capacity. These findings will strengthen Maringgit Village’s potential as a hub for the MSME-based halal industry and also support the achievement of sustainable development goals (SDGs) 9 and 12.